2021
DOI: 10.1186/s12913-021-07025-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic testing for adverse drug reaction prevention: systematic review of economic evaluations and the appraisal of quality matters for clinical practice and implementation

Abstract: Background Genetic testing has potential roles in identifying whether an individual would have risk of adverse drug reactions (ADRs) from a particular medicine. Robust cost-effectiveness results on genetic testing would be useful for clinical practice and policy decision-making on allocating resources effectively. This study aimed to update a systematic review on economic evaluations of pharmacogenetic testing to prevent ADRs and critically appraise the quality of reporting and sources of evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 94 publications
(359 reference statements)
0
6
0
Order By: Relevance
“…That is not the focus of our work. To estimate the costs of testing, we encourage the reader to access other publications, in which PGx testing has been studied and modeled at a population scale (7)(8)(9)(10)(11)27). Rather, our goal in this project was to complement the existing data by incorporating a novel aspect to the analysis: understanding how patient population, demographics, structure of the testing program, and IT costs impact the cost-effectiveness of PGx-CDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is not the focus of our work. To estimate the costs of testing, we encourage the reader to access other publications, in which PGx testing has been studied and modeled at a population scale (7)(8)(9)(10)(11)27). Rather, our goal in this project was to complement the existing data by incorporating a novel aspect to the analysis: understanding how patient population, demographics, structure of the testing program, and IT costs impact the cost-effectiveness of PGx-CDS.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical decision support (CDS) is a critical component for integrating PGx data into the prescribing process, as a provider placing a medication order may not be trained in the interpretation of PGx results (6) and is also unlikely to be aware of a patient's genotype unless they have intentionally sought out that information (4). Multiple studies have examined the cost-effectiveness of PGx for various drug-gene pairs (7)(8)(9)(10)(11), but these studies generally focus on testing and/or medication costs and do not take into account the contribution of CDS to these programs' costs and bene ts (12).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cost-effectiveness studies have been conducted separate from implementation initiatives and they indicate that PGx testing results in a reduction in per-patient treatment cost (Winner et al, 2015 ; Deenen et al, 2016 ), lower cost-per-QALY (Mitropoulou et al, 2015 ) and cost savings in long-term care (Saldivar et al, 2016 ). A recent systematic appraisal of economic evaluations of PGx testing to prevent ADRs found a number of deficiencies in the quality of data used in cost-effectiveness and cost-utility analyses (Turongkaravee et al, 2021 ). Of the 14 economic evaluation studies of CYP2C9 and VKORC1 testing, 10 studies showed that CYP2C9 and VKORC1 testing would be a variably cost-effective and four studies suggested otherwise (Turongkaravee et al, 2021 ).…”
Section: Pgx Implementationmentioning
confidence: 99%
“…A recent systematic appraisal of economic evaluations of PGx testing to prevent ADRs found a number of deficiencies in the quality of data used in cost-effectiveness and cost-utility analyses (Turongkaravee et al, 2021 ). Of the 14 economic evaluation studies of CYP2C9 and VKORC1 testing, 10 studies showed that CYP2C9 and VKORC1 testing would be a variably cost-effective and four studies suggested otherwise (Turongkaravee et al, 2021 ). In contrast, all nine economic evaluation studies of CYP2C19 testing before prescription of clopidogrel ACS patients undergoing PCI showed that CYP2C19 testing would be a potentially cost-effective treatment strategy for avoiding MACE.…”
Section: Pgx Implementationmentioning
confidence: 99%
“…As widely demonstrated by recent studies, the individual response to drugs is a multifactorial condition, depending on the interaction between environmental and genetic factors. An insufficient response to drug treatment can cause a partial or total failure of the current therapy, while an excessive response can cause serious and sometimes fatal side effects and adverse reactions [7].…”
mentioning
confidence: 99%